Potential Of Lactobacillus sp. Supernatan To Control The Growth Of Aspergillus flavus FNCC6109 In Chicken Feed Concentrate - Bimantara, Dandy; Ramona, Yan; Ermayanti, N.G.A Manik (Metamorfosa: Journal of Biological Sciences, 2020)
The main objective of this research was to investigate the potential of Lactic Acid Bacterial isolates and their supernatants, isolated from yoghurt and kefir, to control the growth of A. flavus FNCC6109 in chicken feed concentrate. The experiments were conducted both In vitro and directly applied to chicken feed concentrate. The results showed that two Lactic Acid Bacterial were successfully isolated, identified and both showed initial potential to be developed as biocontrol of A. flavus FNCC6109. Only one best isolate (isolate I) was used in the further investigation. Percentage of growth reduction of A. flavus FNCC6109 in the chicken feed concentrate treated with 30%(v/v) of Lactobacillus sp. supernatant was 72% lower than control (chicken feed concentrate without addition of Lactobacillus sp. I). Keywords : Lactobacillus sp., Aspergillus flavus FNCC6109, chicken concentrate feed